Development of a National Echocardiography Quality Improvement Programme: insights into feasibility, uptake, and clinical utility. (9th January 2014) - Bhattacharyya, Sanjeev; James, Rachael; Rimington, Helen; Allen, Jane; Lee, Lorraine; Fox, Kevin; Masani, Navroz D; Lloyd, Guy; ,
Abstract: Aims: There are minimal data on methods to measure and improve quality in image interpretation when reporting cardiovascular imaging studies. We sought to identify the feasibility and clinical utility of a nationally implemented quality assurance (QA) process. Methods and results: A web-based platform was developed to administer a national QA module to 27 echocardiography departments within the UK. Three QA modules were delivered from 2011. The proportion of units using the QA module increased from 14 (52.2%) in the first module to 22 (81.5%) in the third module. There was no significant change in the proportion of correct answers between the first module (88.9%) and the third module (82.8%), P = 0.3. The number of echocardiographers with at least one incorrect answer increased from 16 (21.6%) in the first module to 54 (34%) in the third module, P = 0.03. Overall, in valvular heart disease cases there were 36 (10.6%) incorrect responses where qualitative assessment of the severity of valve dysfunction was tested compared with 4 (3.6%) incorrect responses where quantitative assessment of valve dysfunction was tested, P = 0.04. In chamber quantification cases, there were 36 (6.8%) incorrect responses where qualitative assessment of chamber function was tested compared with 3 (2.1%) incorrect responses where quantitative assessment of chamber function was tested, P = 0.04. Conclusion: The incorporation of national QA programme is feasible with rapid uptake. The platform allows comparison of an individual's interpretation skills against a reference standard which can be used as a method to identify inter-observer variability and as a training tool.